Spider diagram with greenness assessment criteria for mathematical UV spectrophotometric methodologies for separating overlaid spectrum signals of diclofenac sodium and lidocaine hydrochloride - Hani M Hafez; Alaa Ahmed Mostafa; Omar M El-Abassy (Green Analytical Chemistry)
Diclofenac sodium is a non-steroidal anti-inflammatory medicine (NSAID) used to alleviate pain and inflammation in different circumstances. Lidocaine HCl is a local anesthetic that blocks the formation and transmission of impulses from the nerves along nerve fibers and endings. This paper describes the creation and verification of four spectrophotometric methods that are reliable, exact, and selective for quantifying the concentration of these medications in both their powdered and pharmaceutical form. The concentration of diclofenac sodium was directly estimated at a wavelength of 286 nm. The available techniques for the determinatin of lidocaine HCl include Method I, which is based on first derivative analysis; Method II, which uses first derivative ratio analysis; and Method III, which uses dual wavelength analysis. The techniques parameters were verified in compliance with ICH guidelines. These included the direct determination of diclofenac sodium in the range of 5-35 µg/mL and 60–600 µg/mL concentration range for the first derivative, first derivative ratio, and dual wavelength for the determination of lidocaine HCl. These techniques are highly environmentally friendly, according to the Analytical GREEnness Metric approach (AGREE), Modified Green Analytical Procedure Index (MOGAPI), spider diagram, and Green Solvents Selecting tool.